Analysis of chloride resistance in light weight concrete made from fly ash and bottom Ash - Kola P.; Saloma; Aminuddin K.M.; Usman F. (Accent Social and Welfare Society, 2024)
The coal combustion process at the steam power plant will produce around 5% of fly ash and bottom ash (FA-BA) waste. The FA-BA produced is a fraction of coal that cannot be burned and is a solid waste that can pollute the environment. In this research, modification of lightweight concrete was carried out by using fly ash waste as a substitute for Portland cement and bottom ash waste as a fine aggregate substitute. Furthermore, the lightweight concrete was tested for hydrochloride acid (HCl) resistance with a potential of hydrogen (pH) range of 6-8 with 3 test conditions. The percentage of fly ash waste used as a substitute for cement was 10%, 20%, 30%, and 40% of the total weight of cement and bottom ash waste used as a substitute for fine aggregate was 30%, 40% and 50% of the total weight fine aggregate. The test results for the lightweight concrete composition which has the lightest specific gravity are found in the FL40BO50 of 1.70 gr/cm3 with the minimum compressive strength of 15.92 MPa, while the specimen which has the most optimal specific gravity is found in the FL20BO30 mixture. that is equal to 1.84 gr/cm3 with the most optimal compressive strength of 25.17 MPa. The test results for resistance to HCl, lightweight concrete with a mixture of FL20BO30 experienced the minimum mass loss and the FL40BO50 mixture experienced a maximum decrease in mass, where in testing conditions 1, lightweight concrete experienced a mass decrease of 0.36% up to 1.61% of the initial mass. In case of testing conditions 2, lightweight concrete has decreased in mass by 0.65% to 3.50% of the initial mass. As for testing condition 3, lightweight concrete experienced a mass decrease of 1.03% to 4.81% of the initial mass. This decrease in mass is due to the lightweight concrete experiencing microcrack which is caused by the chloride content in the HCl solution attack the bonding mechanism in lightweight concrete. 2023 Panca Kola et al.